Key Considerations for Phase 2 or 3 Clinical Study Design of Anti-Inflammatory Agent for COVID-19 Treatment - Park, Yewon; Na, Joo Young; Cho, Joo-Youn; Oh, Jaeseong; Rhee, Su-jin (Frontiers in Pharmacology, 2022)
Current understanding of COVID-19 disease progression suggests a major role for the “cytokine storm” as an important contributor to COVID-19 mortality. To prevent an exaggerated immune response and improve COVID-19 patient endpoints, anti-inflammatory therapeutics have been proposed as clinically useful in severe patients with COVID-19. The purpose of this study was to propose a clinical trial design for the development of anti-inflammatory agents for the treatment of COVID-19, taking into account the physiological and immunological process of COVID-19 and the treatment mechanism of anti-inflammatory agents. We reviewed and analyzed the guidelines for the development of COVID-19 treatments and the treatment of COVID-19 by regulatory agencies and previously conducted clinical trials on anti-inflammatory drugs for COVID-19. Finally, after discussing with an advisory group, a synopsis was presented for an example protocol for a COVID-19 anti-inflammatory agent phase 2 or 3 study that considers the drug mechanism and the disease progression of COVID-19. A randomized, placebo-controlled, double-blind parallel-group design was suggested as a phase 2 or 3 trial design for developing an anti-inflammatory agent as a COVID-19 treatment. A key item of the example protocol specific to anti-inflammatory agents was the inclusion and exclusion criteria, taking into account the immunosuppressive effects of the drug, clinical time course of COVID-19 disease, and treatment guidelines for COVID-19. Time to recovery is the primary endpoint associated with clinical efficacy and is generally well accepted by many experts. Through this suggested phase 2 or 3 study design of an anti-inflammatory drug for COVID-19, we provide a basis for a study design that can be utilized in clinical development by pharmaceutical companies which are developing a potential anti-inflammatory agent for COVID-19.